The complete idiot's guide to recession-proof careers - Cohen, Jeff (Jeffrey Fred), 1973- (New York : Alpha, 2010)
Provides tips and insider info to help you find a job that will survive stock market swings and budget cuts.
Includes bibliographical references (p. [303]-304) and index.
Keywords: Vocational guidance -- United States -- Handbooks, manuals, etc; Occupations -- United States